2017
DOI: 10.1371/journal.pgen.1007112
|View full text |Cite
|
Sign up to set email alerts
|

In vivo zebrafish morphogenesis shows Cyp26b1 promotes tendon condensation and musculoskeletal patterning in the embryonic jaw

Abstract: Integrated development of diverse tissues gives rise to a functional, mobile vertebrate musculoskeletal system. However, the genetics and cellular interactions that drive the integration of muscle, tendon, and skeleton are poorly understood. In the vertebrate head, neural crest cells, from which cranial tendons derive, pattern developing muscles just as tendons have been shown to in limb and trunk tissue, yet the mechanisms of this patterning are unknown. From a forward genetic screen, we determined that cyp26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 36 publications
7
49
0
Order By: Relevance
“…Previous studies showed that NCC have a critical role in the acquisition of cranial muscle morphology McGurk et al, 2017;Shimizu et al, 2018;Tokita and Schneider, 2009;von Scheven et al, 2006). Our data using the Rare CreERT2 reporter and following invalidation of Rarb/Rarg in NCC derivatives suggest that the action of retinoic acid signaling on EOM patterning is also indirect, through its action on periocular connective tissues.…”
Section: Ra Responsiveness On the Pomsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies showed that NCC have a critical role in the acquisition of cranial muscle morphology McGurk et al, 2017;Shimizu et al, 2018;Tokita and Schneider, 2009;von Scheven et al, 2006). Our data using the Rare CreERT2 reporter and following invalidation of Rarb/Rarg in NCC derivatives suggest that the action of retinoic acid signaling on EOM patterning is also indirect, through its action on periocular connective tissues.…”
Section: Ra Responsiveness On the Pomsupporting
confidence: 56%
“…Although early myogenesis is NCCindependent, NCC later regulate the differentiation and segregation of muscle precursors, dictate the pattern of muscle fiber alignment, and that of associated skeletal and tendon structures Ericsson et al, 2004;Noden, 1983b;Rinon et al, 2007;Tokita and Schneider, 2009;von Scheven et al, 2006). Moreover, studies of mouse mutants in which several genes were deleted in NCC cells have explicitly demonstrated their non-cell autonomous role in muscle morphogenesis at the level of the jaw (McGurk et al, 2017;Rinon et al, 2007;Shimizu et al, 2018), extraocular (Evans and Gage, 2005;Heude et al, 2015) and somitic-derived tongue muscles (Iwata et al, 2013). However, the full series of events driving morphogenesis of craniofacial musculoskeletal functional units is to date unexplored, probably due to the anatomical complexity of their configuration in the head.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Except for trunk axial muscles, myoblasts leave their sites of initial differentiation and move, usually as aggregated cohorts, into peripheral regions (reviewed by: Noden & Francis‐West, ; Tzahor & Evans, ). This process and (3) the subsequent myotube alignment, segregation of individual muscles, and attachment of myotubes to definitive connective tissues require “instructive” interactions from adjacent connective tissues (limbs: Kardon, ; Kardon, Harfe, & Tabin, ; Robson, Kara, Crawley, & Tickle, ; diaphragm: Merrell et al, ; jaw: McGurk et al, ; reviewed by: Chal & Pourquié, ; Deries & Thorsteinsdóttir, ). In some cases, those interactions are associated with differentiating cartilages or tendons, but often the cues are operating at earlier stages and are more cryptic, identified only through analyses of local transcription factors, for example, Tbx4 and Tbx5 genes in limb mesenchyme (Hasson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Is timing in each tissue independently controlled, or does a common signal regulate the development of both tissues? RA is essential for multiple aspects of PA development (Kopinke et al, 2006;Li et al, 2012;Linville et al, 2009;Mark et al, 2004;McGurk et al, 2017) and changes in RA signaling are thought to contribute to the craniofacial defects in DiGeorge syndrome (Karpinski et al, 2014). Whether RA controls the timing of PA emergence and/or hgfa expression, thereby entraining PA development to RA-regulated events in the vagus motor nucleus, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%